2014
DOI: 10.2139/ssrn.2419031
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Expectations in the Provision of Public Goods Under the Influence of Social Identity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Rather than economic status, people might quite well look at themselves predominantly as members of a particular social community, such as family, neighbourhood, tribe, ethnicity, or religious community. Scholars have shown that a common social identity increases in-group cooperation for the production of a common good (Lankau et al, 2014). If this holds true for the context of a health crisis, we would assume those individuals emphasizing a communal identity – based on allegiance to tribe, ethnic group, or religious community – would be driven by in-group solidarity.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Rather than economic status, people might quite well look at themselves predominantly as members of a particular social community, such as family, neighbourhood, tribe, ethnicity, or religious community. Scholars have shown that a common social identity increases in-group cooperation for the production of a common good (Lankau et al, 2014). If this holds true for the context of a health crisis, we would assume those individuals emphasizing a communal identity – based on allegiance to tribe, ethnic group, or religious community – would be driven by in-group solidarity.…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…As Figure 1 shows, the presence of BP institution eliminates the often documented downward trend of contributions over time (see Fehr and Gächter 2000;Keser and van Winden 2000;Vyrastekova 2011;Lankau et al 2013), independent of the social environment. The average contributions of the first period range between 55% and 68% of total endowment.…”
Section: Contributions To the Public Good And The Level Of Social Welmentioning
confidence: 91%
“…Experimental research has shown that contributions to common goods decrease over time (see e.g. Keser and van Winden 2000, Fischbacher and Gächter 2010, Lankau et al 2013. Nevertheless, the possibility of peer-punishment imposed by group members without a central authority has been investigated as an effective institution providing incentive for compliance and enforcing long-term cooperation in social dilemma games.…”
Section: Introductionmentioning
confidence: 99%